PERAN KELUARGA DALAM PEMBENTUKAN NILAI-NILAI AGAMA PADA ANAK USIA DINI - Masriah, Siti; Nurlaeli, Acep; Akil, Akil (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This journal discusses the role of the family in shaping religious values in young children. Religious values play a crucial role in shaping a child's personality and morals. As the primary unit of socialization, the family has a significant responsibility in introducing and reinforcing religious values to children. This journal elaborates on the factors influencing the role of the family in shaping religious values in young children, as well as strategies that families can employ to achieve this goal. The research is based on a literature review and empirical studies conducted within the context of modern families. The results indicate that positive family interactions, integrated religious education in everyday life, and consistent parental role models in religious practices are key factors in shaping religious values in young children. The journal also discusses the importance of a holistic approach to religious instruction and collaborative efforts among families, religious institutions, and educational institutions to ensure the success of the process of forming religious values in young children.